Blockchain zakat in zakat management organizations, is it necessary? - Nurul Ikhsan (Journal of Enterprise and Development (JED), 2023)
Purpose — This paper aims to analyze whether zakat management organizations need a blockchain zakat system in maintaining transparency of zakat management which can have an impact on increasing the amount of donations collected from muzakki.Method — This research is a qualitative research conducted with descriptive-analytic method through literature study.Result — Zakat management organizations have a duty to ensure transparent management of the funds they collect as public institutions, and therefore must be trustworthy. By adopting a blockchain-based zakat system, these organizations can enjoy various advantages such as trustlessness, immutability, decentralization, lower costs, peer-to-peer transactions, transparency, and universal banking. This technology can also help address existing issues within zakat institutions.Contribution — This study contributes to the existing literature on blockchain-based zakat system which is still rarely to be discussed.